TEM analysis of coplanar stripline moisture sensor - Khalid, K. B.; Maclean, T. S. M.; Razaz, M.; Webb, P. W. (Malaysian Institute of Physics, 1988)
This paper is concerned with the TEM analysis of coplanar stripline moisture sensor by using a numerical technique. The information available is important for the optimum design of this sensor. The calculated results showed that the effective dielectric constant and characteristic impedance were drastically affected by a small thickness of covering layer and a gap in the coplaner stripline structure.